Noise-sensitive measure for stochastic resonance in biological oscillators - Ying-Cheng Lai; Kwangho Park (Mathematical Biosciences and Engineering)
There has been ample experimental evidence that a variety ofbiological systems use the mechanism of stochastic resonance for tasks suchas prey capture and sensory information processing. Traditional quantities forthe characterization of stochastic resonance, such as the signal-to-noise ratio,possess a low noise sensitivity in the sense that they vary slowly about theoptimal noise level. To tune to this level for improved system performance ina noisy environment, a high sensitivity to noise is required. Here we show that,when the resonance is understood as a manifestation of phase synchronization,the average synchronization time between the input and the output signal hasan extremely high sensitivity in that it exhibits a cusp-like behavior aboutthe optimal noise level. We use a class of biological oscillators to demonstratethis phenomenon, and provide a theoretical analysis to establish its generality.Whether a biological system actually takes advantage of phase synchronizationand the cusp-like behavior to tune to optimal noise level presents an interestingissue of further theoretical and experimental research.